REBUILT LOCAL MARGINALIZATION PARTICIPATION IN RIAU ISLAND AS BORDER REGION - Fitrisia Munir (UIR Press, 2020)
This study aims to evaluate the level of marginalization of local communities and analyze their participation in the sustainable development of several cities in the Riau Islands (Batam and Bintan in particular) as a developing industrial city and directly adjacent to ASEAN countries. The qualitative descriptive research method uses a case study approach and develops the gentrification concept in the Riau Islands as an implication of a new industrial city that describes a phenomenon empirically. The results showed that Batam and Bintan as one of the developing industrial cities in the border area between Malaysia and Singapore, have influenced the urban system on a national, regional and global scale. The strong support from globalization has resulted in a strong strategy in a more macroscopic framework, the collaboration of various non-state and sub-state actors so that local communities are not increasingly marginalized compared to immigrant communities in industrial cities that are growing rapidly.